Using Campinha-Bacote’s Framework to Examine Cultural Competence from an Interdisciplinary International Service Learning Program - Wall-Bassett, Elizabeth DeVane; Hedge, Archana V.; Craft, Katelyn; Oberlin, Amber (Journal of International Students, 2018)
The purpose of this study was to investigate an interdisciplinary international service learning program and its impact on student sense of cultural awareness and competence using the Campinha-Bacote’s (2002) framework of cultural competency model. Seven undergraduate and one graduate student from Human Development and Nutrition Science disciplines participated in the program. Reflections from a synthesis paper post-travel were analyzed using an inductive approach. Six themes emerged from the reflective journals and were applied to Campinha-Bacote’s cultural competency constructs. Participating and learning together while reflecting helped deepen and progress this process for ISL students. Overall, the experience proved to be an effective educational tool for sensitizing students towards cultural competency within interdisciplinary programs.